Journey into America the challenge of Islam - Ahmed, Akbar S.; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2010)
"Examines American identity as influenced by its founding and history and the diverse Muslim experience in America, as well as the experience of other religious groups, and how each has affected the other"--Provided by publisher.
pt. 1. American identity -- pt. 2. Islam in America -- pt. 3. Adjusting and adapting.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Muslims -- United States -- Social conditions; Muslims -- United States -- Ethnic identity; Muslims -- Cultural assimilation -- United States; Islam and culture -- United States; Cultural pluralism in Islam -- United States; Islam and civil society -- United States; United States -- Religious life and customs; United States -- Social life and customs; Electronic books